Developments in the Implementation of Acoustic Droplet Ejection for Protein Crystallography. (February 2016) - Wu, Ping; Noland, Cameron; Ultsch, Mark; Edwards, Bonnie; Harris, David; Mayer, Robert; Harris, Seth F.
Acoustic droplet ejection (ADE) enables crystallization experiments at the low-nanoliter scale, resulting in rapid vapor diffusion equilibration dynamics and efficient reagent usage in the empirical discovery of structure-enabling protein crystallization conditions. We extend our validation of this technology applied to the diverse physicochemical property space of aqueous crystallization reagents where dynamic fluid analysis coupled to ADE aids in accurate and precise dispensations. Addition of crystallization seed stocks, chemical additives, or small-molecule ligands effectively modulates crystallization, and we here provide examples in optimization of crystal morphology and diffraction quality by the acoustic delivery of ultra-small volumes of these cofactors. Additional applications are discussed, including set up of in situ proteolysis and alternate geometries of crystallization that leverage the small scale afforded by acoustic delivery. Finally, we describe parameters of a system of automation in which the acoustic liquid handler is integrated with a robotic arm, plate centrifuge, peeler, sealer, and stacks, which allows unattended high-throughput crystallization experimentation.